2006
DOI: 10.1007/bf03219097
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of crosslinkable waterborne polyurethanes containing aminoplast(I)

Abstract: A series of crosslinkable, waterborne polyurethanes (I-WBPUs) were prepared by in-situ polymerization using isophorone diisocyanate (IPDI)/poly(tetramethylene oxide) glycol (PTMG, M n =2,000)/ dimethylol propionic acid (DMPA)/ethylene diamine (EDA)/triethylamine (TEA)/aminoplast [hexakis(methoxymethyl)melamine (HMMM)] as a crosslinking agent. Typical crosslinkable, waterborne polyurethanes (B-WBPUs) blended from WBPU dispersion and aqueous HMMM solution was also prepared to compare with the I-WBPUs. The crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In literature, many types of PUs based on a number of diols and diisocyanates have been prepared and studied for various applications. [3][4][5][6][7][8][9][10] The hard segments can also be based on polyester 11 or polyamide. 12 At ambient temperatures, the hard segments are incompatible with the soft segments.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, many types of PUs based on a number of diols and diisocyanates have been prepared and studied for various applications. [3][4][5][6][7][8][9][10] The hard segments can also be based on polyester 11 or polyamide. 12 At ambient temperatures, the hard segments are incompatible with the soft segments.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the viscosity of the dispersions increases with increasing HMMM content. This increase in viscosity might be due to stiff polyurethane chains in the crosslinked structure [17]. The viscosity of HMMM-crosslinked WBPU with excess HMMM content was lower than that of the observed optimum HMMMcrosslinked WBPU dispersion.…”
Section: Resultsmentioning
confidence: 96%
“…To improve these properties, significant efforts have been made during the last decade with various approaches such as using a higher 2,2-dimethylol propionic acid (DMPA) content, using poly(tetramethylene adipate glycol), incorporating an aliphatic hardener, blending and crosslinking. [1][2][3] Recently the thermal and mechanical properties were improved by making various WBPUnanocomposites. 4 Recent years have seen a rapid upsurge of silane technology in the field of corrosion and antifouling coatings.…”
Section: Introductionmentioning
confidence: 99%